First report of Lasiodiplodia theobromae associated with panicle blight of grapes (Vitis vinifera L.) in India - Mahadevakumar, S; Joy, Josna; Mamatha Bhanu, L S; Niranjan Raj, S; Sharvani, K A; Sowmya, R; Chandranayaka, S (Plant disease, 2023)
Grape (Vitis vinefera L.) is a popular horticulture crop in Karnataka, India. A fungal pathogen caused panicle blight on panicles with immature fruit and severity increased subsequently in the grape growing regions of Devanahalli and Doddaballapur, Karnataka, between August and September 2019. The disease incidence varied from 15 to 18 percent in around 45 hectares of grape vineyards surveyed. The associated fungal pathogen was isolated on Potato Dextrose Agar (PDA) medium (HiMedia Laboratory, Mumbai, India) amended with Chloramphenicol. A total of 12 fungal isolates were obtained and identified based on morphology. Fungal cultures obtained from all the panicle blight affected samples were fluffy grayish to black with profuse, dense mycelium. Microscopic examinations revealed that the conidia ellipsoidal, two celled and hyaline when young, and developed dark brown pigments at maturity. Mature conidia measured 18.24±2.35 to 26.62±3.11 μm long and 10.32±1.08 to 12.57±1.82 μm width (n=30). The fungal pathogen was identified as a Lasiodiplodia sp. based on colony morphology and microscopic features. A total of three representative isolates L. theobromae (Vv12, Vv15, and Vv19) were selected for molecular identification based on ITS-rDNA, tub2 and EF-1α gene sequences and phylogenetic analysis. Genomic DNA was isolated from 12 day old cultures and ITS-rDNA, tub2 and EF-1α genes were amplified using ITS1/ITS4; Bt2a/Bt2b and EF1-728F/986R primer pairs, respectively (White et al., 1990; Glass and Donaldson, 1995, Carbone and Kohn, 1999). PCR amplicons were sequenced and the sequences were deposited in GenBank with the accession number ITS: MZ855866.1; MZ855867.1; MZ855868.1; tub2: MZ868708.1; MZ868709.1; MZ868710.1 and EF-1α: OM604750; OM604751; OM604752 respectively. The phylogeny was constructed based on combined ITS, EF-1α and the tub2 regions. Maximum Likelihood (ML) analysis was conducted and an ML tree was constructed with the substitution models (branch support was evaluated by 1,000 bootstrap replications). Combined phylogeny confirmed that the sequences shared a common clade with L. theobromae. Based on micro-morphological features and multi-locus sequence phylogeny, the associated fungal pathogen was identified as L. theobromae. There are no reports on the occurrence of L. theobromae causing panicle blight on grapes from India. Further, the pathogens association was confirmed through pathogenicity assay conducted on field harvested healthy bunches of grapes maintained under humid chamber. A total of 10 grape bunches were inoculated with a mycelial disc on the rachis of the panicle and incubated in a moist chamber for 5 days and control sets were inoculated with only agar plugs. The experiments were conducted in three replicates and repeated twice. A total of 21 panicle bunches developed typical rot symptoms 12-days post inoculation. The identity of the pathogen was confirmed based on micromorphology and cultural features after re-isolation (n=5), thus proving the Koch postulates and confirming the association of L. theobromae with panicle blight of grapes. Lasiodiplodia species are known to cause dieback, stem blight, leaf blights and spots on various crop plants. Mathur (1979) mentioned the occurrence of L. theobromae on grapes, however, no further details are available on the part associated, as well as morphological and molecular confirmation of L. theobromae. This is the first report of the L. theobromae causing panicle blight disease of grapes in India. Further, understanding the host range for L. theobromae and its variation will help to draw suitable disease management strategies.